Biotechnology learning profile biology in FKIP Biology Education Study Program Pasundan University Bandung Indonesia. (March 2020) - Halimah, M; Rahmat, A; Redjeki, S
Abstract: Life in the 21 st century requires a variety of skills that must be mastered by everone. Achieving 21 st century skills is done by updating the quality of learning, one of which is learning Biotechnology. Biotechnology is one of the subjects taught in the Biology Education Study Program FKIP UNPAS Bandung which is taught to provide students as Biology teacher candidates who have academic abilities that can apply, develop and disseminate science and technology professionally. The purpose of this study was to determine the learning process of biotechnology that took place for students of Biology teacher candidates in the Biology Education Study Program, FKIP Unpas. The method used is descriptive qualitative with a questionnaire consisting of 18 questions which are a mixture of questions in open and closed forms and also interviews. Some 38 students and 2 lecturers were involved in this study. The results of the study show that the learning process in the Biology Education Study Program, FKIP UNPAS, still uses the classical method with a teaching-centered learning system. But the enthusiasm of the teaching staff to develop themselves is very potential to encourage the improvement of the quality of the learning process in the near future. Evidently, although it is still centered on the instructors, lecturers have used a scientific approach, PPA models and power point media equipped with animated videos.